Level of Attack of Ganoderma boninense on Palm Oil Plant in Different Topographies - Sri Ngapiyatun; Satriady Ramdhani; Wartomo; Humairo Aziza (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
This research was motivated by the stem rot disease of Ganoderma boninense. Symptoms of Ganoderma disease attack young and old plants aged 10-25 years, as a result of this attack, the production of oil palm fruit bunches decreases. This research aims to determine the symptoms of Ganoderma attacks on oil palm plants, and determine the highest level of Ganoderma attacks in different topography, namely hilly, flat and swampy. This research uses samples of oil palm plants by determining saturated sampling, namely taking samples of oil palm plants in all topography, including hilly, flat and swampy, with a total of 15 blocks in Division 4, with 5 blocks in each topography. Data collection uses primary and secondary data. The data analysis used was by calculating the percentage of attacks and using a completely randomized design (RAL) test. The research results show that the oil palm plants at PT. Rea Kaltim Plantations, Estate Sentekan Main in Division 4 has symptoms of Ganoderma boninense attacks. The highest percentage of Ganoderma boninense attacks is found in the swamp topography (17.08%). Based on ANOVA test, the topography gives a significant effect on the percentage of Ganoderma attacks.